Perspectives of Development and Enhancement of the Efficiency of the Functioning of Small Forms of Business on the Village - Vadym Tkachuk; Oksana Vitriak (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article substantiates the prospects for the development and increase of the functioning efficiency of small farming forms in the countryside. Particular attention is paid to the study of factors that have a negative impact on the farms and households functioning. Based on the analysis of statistical indicators, it has been established that the most significant factors that have a negative impact on the functioning of small farming forms in the countryside are the difficulty of manufactured products realization, insufficiently effective state support, lack of developed infrastructure, low education level of households' heads. In order to minimize the negative impact of the identified range of problems, it is proposed to introduce preventive measures in the following areas: the state support system improvement, infrastructure development, the production base and resource support improvement, integration relations development.